2017
DOI: 10.1093/hmg/ddx421
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathy-associated mutations of IFT122 impair ciliary protein trafficking but not ciliogenesis

Abstract: The intraflagellar transport (IFT) machinery containing the IFT-A and IFT-B complexes mediates ciliary protein trafficking. Mutations in the genes encoding the six subunits of the IFT-A complex (IFT43, IFT121, IFT122, IFT139, IFT140, and IFT144) are known to cause skeletal ciliopathies, including cranioectodermal dysplasia (CED). As the IFT122 subunit connects the core and peripheral subcomplexes of the IFT-A complex, it is expected to play a pivotal role in the complex. Indeed, we here showed that knockout (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 49 publications
12
59
0
Order By: Relevance
“…1 E–G) was different between the control and IFT22 -KO cells. As described previously ( Hirano et al, 2017 ), IFT88 was localized mainly around the base of cilia and faintly along cilia, and IFT140 was mainly found around the ciliary base; note that, as described previously ( Hirano et al, 2017 ; Takahara et al, 2018 ), the commercially available polyclonal antibody against IFT140 also stained undetermined structures in the nucleus of RPE1 cells; see the manufacturer's website ( ).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…1 E–G) was different between the control and IFT22 -KO cells. As described previously ( Hirano et al, 2017 ), IFT88 was localized mainly around the base of cilia and faintly along cilia, and IFT140 was mainly found around the ciliary base; note that, as described previously ( Hirano et al, 2017 ; Takahara et al, 2018 ), the commercially available polyclonal antibody against IFT140 also stained undetermined structures in the nucleus of RPE1 cells; see the manufacturer's website ( ).…”
Section: Resultssupporting
confidence: 56%
“…The strategy of CRISPR/Cas9-mediated gene disruption of hTERT-RPE1 cells using homology-independent DNA repair was previously reported in detail ( Katoh et al, 2017 ); also see ( Funabashi et al, 2017 ; Hirano et al, 2017 ; Nishijima et al, 2017 ; Nozaki et al, 2018 , 2017 ; Takahara et al, 2018 ). Single guide RNA (sgRNA) sequences targeting the IFT22 gene or those targeting both the IFT70A and IFT70B genes (see ) were designed using CRISPR design ( Hsu et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…In considerable contrast, in WDR60 -KO cells, IFT88 was observed throughout cilia and often found around the distal tips ( Figure 4B ; also see Figure 4I ); this phenotype is reminiscent of that of IFT139 -KO and IFT121 -KO cells ( Hirano et al. , 2017 ; Takahara et al. , 2018 ); both IFT139 and IFT121 are peripheral subunits of the IFT-A complex and are encoded by the causative genes of SRTD ( SRTD4 and SRTD7 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Functional analysis showed that ift122 knockdown in zebrafish embryos leads to reduced number of basal bodies and cilia in the pronephric duct and shorter primary cilia of Kupffer vesicles. In human HEK293T cells IFT122 knockout leads to cilia loss [129][130][131][132], while Wdr35 knockout in mouse fibroblasts reveals strongly reduced level of IFT43 [133]. Human and mouse fibroblasts lacking WDR35 fail to produce cilia [134].…”
Section: Sensenbrenner Syndromementioning
confidence: 99%